Central venous oxygen saturation is not a predictor of extubation success after simple weaning from mechanical ventilation in post-cardiac surgical patients - Kaweesak Chittawattanarat (2018)
© 2016, Medical Association of Thailand. All rights reserved. Objective: Central venous oxygen saturation (ScvO2) is a measure of the balance between oxygen delivery and consumption. The purpose of this study was to evaluate whether ScvO2 predict weaning success and extubation in simple weaning postcardiac surgical patients. Material and Method: We prospective observed critically ill post-cardiac surgical patients who were intubated and mechanically ventilated between December 2011 and October 2014. All enrolled patients underwent a spontaneous breathing trial (SBT) before extubation. Arterial and venous blood gas analysis, and hemodynamic and ventilator variables were recorded at the beginning of SBT (T1) and before extubation (T2). Weaning success was defined as successful extubation after SBT without re-intubation within 48 hours. The area under the receiver characteristic curve (ROC) demonstrated the ability to discriminate weaning success. Statistical significance was defined as p<0.05. Results: A total 121 patients were included. Of these, 18 patients (15%) were re-intubation within 48 hours after extubation. There was no statistically significance in age, gender, and type of operations between those who were extubated successfully and those who were re-intubated within 48 hours. Regarding hemodynamic and respiratory parameters, the significant differences were found only in partial arterial oxygen pressure (PaO2; p = 0.048) and PaO2 to oxygen fraction ratio (PF ratio; p=0.048) at T1. There was no difference between the groups in ScvO2 at either T1 or T2. The area under the ROC (95% confidence interval) of ScvO2 was 0.60 (0.47-0.74) and 0.53 (0.39-0.66) at T1 and T2, respectively. Although ScvO2 was combined with rapid shallow breathing index (RSBI), PF ratio and minute volume on the regression model at both T1 and T2, the discrimination ability was not significant increased. Conclusion: ScvO2 or its combination with RSBI, PF ratio and minute volume does not predict successful weaning from mechanical ventilators and extubation in critically ill post-cardiac surgical patients.